Perancangan Laporan Keuangan dan Per[pajakan Berdasarkan SAK EMKM Berbasis Microsoft Excel Dalam Penentuan Laba Pada UMKM Moinies.jbi - Rini Agustin; Johandri Iqbal; Junaidi (LP2M Politeknik Jambi, 2026)
The aims of this study to design a Microsoft Excel-based financial and tax reporting system for MSME Moinies.jbi in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Currently, Moinies.jbi only performs simple manual recording, so it is difficult to determine the accurate profits and fulfill tax obligations as per to Government Regulation Number 55 of 2022. The study uses a descriptive qualitative method through interviews, observation, and documentation. This research designs a digital accounting workflow from journals to financial statements as well as a 0.5% Final Income Tax calculation module. The results show that this Excel-based system design is capable of automatically and accurately generating the Statement of Financial Position, Income Statement, and Notes to Financial Statements (CaLK). The implementation of this model is proven effective in assisting the business owner in determining accountable net profit and simplifying the tax reporting process, serving as a practical solution for MSMEs to overcome human resource limitations in financial management and tax compliance.